The Effect Of Functional Value, Emotional Value, Value For Money On Repurchase Intention Through Customer Satisfaction As An Intervening Variable In Purchasing Virtual Items For Online Games Mobile Legends: Bang-Bang (Study On Mobile Online Game Users Le - Yuliana Yuliana; Nurul Azizah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine the effect of functional value, emotional value, value for money on repurchase intention through customer satisfaction as an intervening variable in purchasing Mobile Legends virtual items: Bang-Bang. This type of research is quantitative research. The sampling technique used non probability sampling with a sample size of 180 respondents. The sample criteria chosen in this study are users of the Mobile Legends application: Bang-Bang in Surabaya who are 16-64 years old and have a history of making purchases at least twice. The data analysis technique in this study used Partial Least Squares (PLS) analysis with SmartPLS 4.0 software. The results in this study indicate that functional value, emotional value and value for money has a positive effect on customer satisfaction. Functional value, emotional value and value for money has a positive effect on repurchase intention. Customer satisfaction has a positive effect on repurchase intention. Keywords: Functional Value, Emotional Value, Value for Money, Repurchase intention, Customer Satisfaction